Field reports form for submitting seasonal observations of Iowa birds - Harms, Ronaldet al (1983)
An annotated list of birds sighted by Ronald Harms. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of Summer 1983. Epson - sheet feed